2018
DOI: 10.2147/cmar.s164227
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs and <em>EGFRvIII</em> sequestered in TEPs enable blood-based NSCLC diagnosis

Abstract: BackgroundTissue biopsy-based cancer diagnosis has limitations because of the fact that tumor tissues are in constant evolution and extremely heterogeneous. The current study was aimed to examine whether tumor-educated blood platelets (TEPs) might be a potential all-in-one source for blood-based cancer diagnostics to overcome the limitations of conventional cancer biopsy.MethodsIn the present study, we evaluated the expression pattern of MAGI2 antisense RNA 3 (MAGI2-AS3) and ZNFX1 antisense RNA 1 (ZFAS1) in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 39 publications
(42 reference statements)
1
35
0
Order By: Relevance
“…15,26 The downregulation of MAGI2-AS3 has been proved in NSCLC including LUAD and LUSC. 16,17 A recent research validated the tumor-suppressive role of MAGI2-AS3 in NSCLC based on LUAD cell lines. 18 However, the role of MAGI2-AS3 in LUSC is yet to be shown.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…15,26 The downregulation of MAGI2-AS3 has been proved in NSCLC including LUAD and LUSC. 16,17 A recent research validated the tumor-suppressive role of MAGI2-AS3 in NSCLC based on LUAD cell lines. 18 However, the role of MAGI2-AS3 in LUSC is yet to be shown.…”
Section: Discussionmentioning
confidence: 95%
“…[13][14][15] Importantly, previous studies have identified that MAGI2-AS3 is down-regulated in NSCLC samples, including LUAD and LUSC samples. 16,17 Moreover, we identified through GEPIA online tool based on TCGA data that MAGI2-AS3 was downregulated in LUSC samples versus normal samples. These findings indicated that MAGI2-AS3 might participate in LUSC.…”
Section: Introductionmentioning
confidence: 99%
“…In NSCLC, the expression of lncRNAs was analyzed in platelets in order to identify novel biomarkers of lung cancer. A selection of five lncRNAs was identified and further measurements revealed a differential expression of two lncRNAs, namely, Membrane-Associated Guanylate Kinase Inverted 2-Antisense RNA 3 ( MAGI2-AS3 ) and Zinc Finger NFX1-Type Containing 1 Antisense RNA 1 ( ZFAS1 ), in platelets of NSCLC patients compared to healthy subjects [ 94 ]. Both lncRNAs have been assigned tumor suppressive functions in human breast cancer [ 95 , 96 , 97 ], whereas ZFAS1 seems to be a potent oncogenic lncRNA in other tumor types [ 98 ].…”
Section: Composition and Sources Of Rna Species In Plateletsmentioning
confidence: 99%
“…In platelets and plasma of NSCLC patients, MAGI2-AS3 and ZFAS1 were downregulated and their expression significantly correlated with tumor stage. In addition, MAGI2-AS3 expression significantly correlated with lymph-node and distant metastasis and the authors suggested that both platelet-derived lncRNAs could be used as potential diagnostic biomarkers in NSCLC [ 94 ]. However, the molecular function of these and other lncRNAs in platelets is currently not well understood and it is tempting to speculate about a potential transfer of lncRNAs from platelets to diverse other cell-types to modulate expression programs and phenotypes.…”
Section: Composition and Sources Of Rna Species In Plateletsmentioning
confidence: 99%
“…Total RNA was extracted using an RNAprep Pure FFPE Kit (TIANGEN Biotech, Beijing, China) according to the manufacturer's instructions. Total RNA of 300 µL serum was isolated by using a Liquid Total RNA Isolation Kit (BioTeke, Beijing, China) as we described previously [27] and treated with DNase I prior to reverse transcription. The concentration of RNA was measured by Nanodrop 2000 spectrophotometer (Thermo Fisher) following puri cation with RNeasy mini kit (QIAGEN).…”
Section: Rna Isolation and Cdna Synthesismentioning
confidence: 99%